Analysis of Student Misconceptions Using Digital Four-Tier Diagnostics Test on Newton's Law - Choirul Huda; Afwania Lutfa Ma’ani; Ummi Kaltsum (Faculty of Science and Education, UIN Walisongo Semarang, 2022)
Research has been carried out on the analysis of student misconceptions using a digital four-tier diagnostic test in physics subjects for newton's law class VIII SMP Hasanuddin 05 Semarang. This study aims to determine the students' misconceptions and the factors that cause misconceptions in Newton's law material. The method used in this research is quantitative descriptive, used to describe the level of students' misconceptions by describing the percentage of the number. The sample in this study was 26 students of class VIII C SMP Hasanuddin 05 Semarang. The research instrument uses four-tier multiple-choice tests, at level 1 and 3 objective tests are questions on the questions and reasons for answers, while levels 2 and 4 contain the level of confidence in the answers and the level of confidence in the reasons for the answers. The sampling technique is purposive sampling. Test the validity by using the Karl Pearson Correlation formula. Reliability test using Alpha Cronbach formula. The results of the validity test showed that of the 15 questions developed, there were 11 valid questions. The reliability test results showed that the instrument is reliable. The research data shows that students of class VIII C SMP Hasanuddin 05 Semarang have misconceptions about Newton's law material. The percentage level of students' misconceptions in class VIII C is 53.85% in the medium category. The main factor that influences the students' misconceptions in class VIII C is the lack of interest in students' learning as a result of the teacher teaching only by using the lecture method and working on questions, and there is no concrete example.